If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 1 + 3x = 46 Reorder the terms: 1 + 6x + 3x = 46 Combine like terms: 6x + 3x = 9x 1 + 9x = 46 Solving 1 + 9x = 46 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + 9x = 46 + -1 Combine like terms: 1 + -1 = 0 0 + 9x = 46 + -1 9x = 46 + -1 Combine like terms: 46 + -1 = 45 9x = 45 Divide each side by '9'. x = 5 Simplifying x = 5
| (2x+4)(3x+5)=0 | | 3x+=30 | | 5x-3+2x=-80 | | 7=3x-x+3 | | -14=-3x+7x+10 | | 20-4x=-6x+12 | | (n-2)180=60 | | -4+4x+6x=-54 | | 7x+6+6x=110 | | t/-12=-4/15 | | -2*-4=5+8 | | -6+6x-4x=16 | | x^2-4ax-2=0 | | -5x+7+2x=-8 | | 1=5x+3x-7 | | 1=p+12 | | 3*-2=5*4-26 | | -21n=483 | | 3sinx+4cosx^2=0 | | r+2=15 | | -3*-2=x+2 | | 2u+10=26 | | (2x-5)(3x+4)= | | 5x(63-16)= | | m^3-6=0 | | (4w-8)(w+3)=0 | | -2in(x)+in(y)=in(6) | | 6x^2-11x-13=5(x^2-1)+3 | | 8+6x=7x-5 | | V+4=-5 | | Y=-16x+20x+5 | | 3X^(7/3)-6=0 |